Initial literature review: achieving operational excellence in SMEs through the integration between continuous improvement and innovation - Sousa, Sérgio (2016)
This paper is an initial literature review of a PhD plan. It will mention the definition and importance of Small and Medium-sized Enterprises (SMEs), and how the integration between Continuous Improvement and Innovation plays a huge role in maintaining and boosting the competitive advantage of SMEs. The aim of this research is to develop an integrated framework that combines the approaches of Continuous Improvement and Innovation. The framework intends to assist SMEs to know what to select from projects that would boost their operational excellence, and also how to sustain the expected results for a long term. The proposed framework shall promote a culture of Continuous Improvement and Innovation. The research will take into consideration SMEs in a particular industry. The research activities will take up to two years and will include case studies and surveys.